2019
DOI: 10.1042/bsr20182279
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy efficacy of Chinese drugs pharmaceutics for COPD patients with respiratory failure: a meta-analysis

Abstract: We performed a meta-analysis to evaluate the efficacy and safety of Western medicine combined with Tanreqing for patients with chronic obstructive pulmonary disease (COPD) and respiratory failure. We comprehensively searched several online databases from the times of their inception to November 2018. The trial quality was assessed using the bias risk tool recommended by the Cochrane library. Relative risks (RRs) and their 95% confidence intervals (CIs) for binary outcomes and weighted mean differences (MDs) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…21 This study attempted to investigate the potential of gastrodin for COPD management. Thus, preventing COPD has become a promising method for COPD management and a small fraction of researches have focused on the beneficial effects of traditional Chinese herbal medicine on this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 This study attempted to investigate the potential of gastrodin for COPD management. Thus, preventing COPD has become a promising method for COPD management and a small fraction of researches have focused on the beneficial effects of traditional Chinese herbal medicine on this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, preventing COPD has become a promising method for COPD management and a small fraction of researches have focused on the beneficial effects of traditional Chinese herbal medicine on this disease. 21 This study attempted to investigate the potential of gastrodin for COPD management. To this end, LPS was applied to treat MRC-5 cells to construct a cell model of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 belongs to the immunoglobulin superfamily and is produced by mononuclear cells (17). This cytokine is involved in the onset and development of COPD, and its level is directly related to the severity of the acute exacerbation of COPD (AECOPD) (18). Imaoka et al showed that serum levels of IL-18 in COPD patients and smokers were significantly higher than nonsmokers (19).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the role of montelukast in reducing IL-1β levels in previous studies (24), and the role of inflammasome and caspase-1 in the production of these two cytokines (IL-1β and IL-18) (25), montelukast probably uses a similar mechanism to reduce the level of IL-18. This may explain the partial inhibitory effect of montelukast on the development of smoke-induced inflammation by reducing some inflammatory cytokines, such as IL- 18.…”
Section: Discussionmentioning
confidence: 99%
“…The main bioactive components in TRQ injection are flavonoids, phenolic acid, and lignans from Scutellaria baicalensis Georgi, Lonicera japonica flos, and Fructus Forsythiae (Wang, Liao, et al, 2016; Wang, Peng, & Zou, 2016). Studies have shown that baicalin, chlorogenic acid and phillyrin have good anti‐inflammatory, antibacterial, and antiviral activities (Feng et al, 2018; Liu, Li, Wang, Lu, & Wang, 2019). Related meta‐analysis found that TRQ injection was effective and safe in the treatment of respiratory tract infections such as pulmonary infection in patients with tuberculosis (Xiong et al, 2018), community‐acquired pneumonia (Huang et al, 2019) and hematological tumor with pulmonary infection (Ai, Xiao, & Wang, 2015).…”
Section: Discussionmentioning
confidence: 99%